PANDANGAN PEMIMPIN GEREJA TENTANG PENGATURAN ORGANISASI GEREJA DI PROVINSI PAPUA - Asnawati Asnawati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study discusses church leader viewpoints on church organization management in Papua. The study uses qualitative approach that aims to describe the religious leaders viewpoints related to services, counseling, and organization management or denomination of church and Christian board by ministry religious affair in Papua. The study describes contributions of Christian leaders’ visionary thought in Papua to establish religious harmony and peacefulness that there are some new denominations to get legalization from the government after determination of Act No.17, 2013 about community organization. The result of study can be concluded that church leaders agree that organization management conducted by ministry religious affair in Papua is good and they have same perception on making a good relationship to make peace in Papua and uphold “satu tungku tiga batu” motto to build strong relationship between adherents and religious leaders. Generally, the relationship between Christians and society around the church as well between church and ministry religious affair is good.